Improving End-User Satisfaction with Electronic Medical Records (EMR) - Agiwahyuanto, Faik; Suyoko, Suyoko; Anjani, Sylvia; Wulandari, Fitria (Jurnal Borneo Administrator, 2025)
In today's interconnected world, it is widely understood that the effectiveness of health information system, a key component of information technology, depends on user satisfaction. In theory, electronic medical records (EMRs) were just a substitute for paper records; nevertheless, they have brought about substantial changes to the working circumstances of nurses and other professionals in the healthcare business. This study introduces a novel approach to improve user satisfaction within Semarang City context, which could potentially be implemented globally. The impact of modern technology was investigated by applying Aggelidis and Chatzouglou's End User Computing Satisfaction (EUCS) approaches to previous health information system (HIS). As a result, the fundamental model was enhanced by including a new factor known as "technology compatibility." This research aims to develop a perspective that can measure the degree of satisfaction experienced by end users. Italso investigates the influence of technical compatibility component, which wasrecently included. Quantitative correlation was chosen as the approach for crosssectional analysis. Approximately 200 participants took part in the study effort. Every single survey question was structured into a five-point Likert scale, which was then reviewed again by specialists from a range of highly specialized fields. The explanatory factor analysis served as the foundation for the final structure of the measuring instrument. PLS-SEM, or partial least structural equation modeling, was used to analyze the data collected by stratified random sampling. As a result, the quality of information, the quality ofsystem, the supporting resources, and the compatibility of technology are all factors that impact user satisfaction. Implementing changes and breakthroughs in information system would increase overall user satisfaction